ChemInform Abstract: Artificial Diiron Enzymes with a de novo Designed Four‐Helix Bundle Structure. Issue 40 (October 2015) - Chino, Marco; Maglio, Ornella; Nastri, Flavia; Pavone, Vincenzo; DeGrado, William F.; Lombardi, Angela
Abstract Review: 174 refs.